Individualising the Western Ontario and McMaster Universities osteoarthritis index (WOMAC) function subscale: incorporating patient priorities for improvement to measure functional impairment in hip or knee osteoarthritis. Issue 4 (17th August 2007) - Seror, R; Tubach, F; Baron, G; Falissard, B; Logeart, I; Dougados, M; Ravaud, P
Abstract : Objective: Recommended outcome measures in osteoarthritis are standardised scales identical for each patient. As patient-specific scales are of increasing interest when considering patient priorities in outcome assessment, this study aims to validate individualised forms of the Western Ontario and McMaster Universities osteoarthritis index (WOMAC) function subscale. Patients and Methods: WOMAC function subscale data were prospectively obtained from 1218 outpatients with hip or knee osteoarthritis requiring non-steroidal anti-inflammatory drugs. Patients also rated the importance to remove disability in each activity of the WOMAC function subscale, and selected the five activities they considered the most important to be improved upon. After treatment, patients again completed the WOMAC function subscale. Several individualisation methods were evaluated: methods whereby the score of each item is multiplied by, or added to, its importance, and methods based on the five most important activities (WOMAC top 5). Psychometric properties of individualised scales were compared to those of the WOMAC function subscale. Results: The missing data rate was 11%, 13% and 2% for the WOMAC function, its individualised forms and the WOMAC top 5, respectively. Combining severity and importance of each item did not improve the properties of the scales. The WOMAC top 5 was the most responsive scale (standardised response mean: 0.96 vs 0.80, p<0.001). Conclusion: Because of its better responsiveness, ease of use, low missing data rate and ability to highlight patient priorities, the WOMAC top 5 could be an interesting tool in therapeutic evaluation in hip or knee osteoarthritis.